2017
DOI: 10.4269/ajtmh.16-0969
|View full text |Cite
|
Sign up to set email alerts
|

Differential Vector Competency of Aedes albopictus Populations from the Americas for Zika Virus

Abstract: To evaluate the potential role of s (Skuse) as a vector of Zika virus (ZIKV), colonized mosquitoes of low generation number (≤ F5) from Brazil, Houston, and the Rio Grande Valley of Texas engorged on viremic mice infected with ZIKV strains originating from Senegal, Cambodia, Mexico, Brazil, or Puerto Rico. Vector competence was established by monitoring infection, dissemination, and transmission potential after 3, 7, and 14 days of extrinsic incubation. Positive saliva samples were assayed for infectious titer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 57 publications
5
91
0
3
Order By: Relevance
“…However, recent in vivo and in vitro experimental work using a limited number of ZIKV strains demonstrated that the African lineage exhibits increased fitness/virulence in vertebrates as well as mosquito vectors compared to Asian lineage strains (Bowen et al, 2017; Weger-Lucarelli et al, 2016; Lazear et al, 2016; Roundy et al, 2017; Azar et al, 2017). Characterization of additional African strains in mosquito vectors, reservoir hosts and models for human infection, including early African isolates not available in reference collections are needed to fully explore the evolution of ZIKV, as well as to identify mutations potentially associated with differing phenotypes.…”
Section: Emergence and Spread Of Zikv Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent in vivo and in vitro experimental work using a limited number of ZIKV strains demonstrated that the African lineage exhibits increased fitness/virulence in vertebrates as well as mosquito vectors compared to Asian lineage strains (Bowen et al, 2017; Weger-Lucarelli et al, 2016; Lazear et al, 2016; Roundy et al, 2017; Azar et al, 2017). Characterization of additional African strains in mosquito vectors, reservoir hosts and models for human infection, including early African isolates not available in reference collections are needed to fully explore the evolution of ZIKV, as well as to identify mutations potentially associated with differing phenotypes.…”
Section: Emergence and Spread Of Zikv Infectionmentioning
confidence: 99%
“…aegypti mosquito (Marchette et al, 1969; Weger-Lucarelli et al, 2016; Roundy et al, 2017; Olson et al, 1981; Guerbois et al, 2016; Li et al, 2012; Boorman and Porterfield, 1956; Cornet et al, 1979b; Hall-Mendelin et al, 2016; Richard et al, 2016; Chouin-Carneiro et al, 2016), and to lesser degree the peridomestic Ae. albopictus (Azar et al, 2017; Grard et al, 2014; Wong et al, 2013), Ae. hensilli (Ledermann et al, 2014) and Ae.…”
Section: Mosquito Transmission and Control Measures (Nikos Vasilakis)mentioning
confidence: 99%
See 2 more Smart Citations
“…19 In fact, Aedes spp. have been detected in these southern states [20][21][22] With this mosquito as their vector, will Dengue, Chikungunya, and Zika continue their rampant spread across the continent? Will yellow fever and Mayaro be the new plagues?…”
Section: Izurieta Et Almentioning
confidence: 99%